Production and Operations Management / Manufacturing and Services: Eighth Edition - Aquilano Nicholas J.; Chase Richard B; Jacobs F. Robert (Irwin Mcgraw-Hill, 1998)
Includes CD-Rom. Nature and Context of Operations Management, Introduction to the Field, Operations Strategy and Competitiveness, Project Management, Product Design and Process Selection - Manufacturing, Operations Technology, Product Design and Process Selection - Services, Waiting Line Management, Quality Management, Statistical Quality Control Methods, Design of Facilities and Jobs, Strategic Capacity Planning, Linear Programming, Just-in-Time Production Systems, Facility Location, Facility Layout, Job Design and Work Measurement, Learning Curves, Managing the Supply Chain, Supply Chain Management, Forecasting, Aggregate Planning, Inventory Systems for Independent Demand, Operations Scheduling, Simulation, Operations Consulting, Business Process Reengineering, Synchronous Manufacturing and Theory of Constraints, Appendixes, Name and Subject Index.